Contemporary outcomes of mitral valve replacement in octogenarians. Issue 3 (25th December 2021) - Tsubota, Hideki; Sakaguchi, Genichi; Arakaki, Ryoko; Marui, Akira
Abstract: Aim of the Study: We aimed to determine the outcomes of contemporary mitral valve replacement (MVR) in octogenarians, for rational treatment selection in a patient cohort. Methods: Between 2007 and 2018, 656 consecutive MVRs were performed. Among these cases, 109 patients were aged 80 years or older, and 547 patients were younger than 80 years. Isolated MVRs were performed in 211 patients, of whom 36 were aged 80 years or older. Perioperative mortality and complications were compared between the two groups, adjusted by propensity score. Results: In‐hospital mortality of the entire MVR (<80: 26 [4.8%] vs. ≥80: 6 [5.5%], p = .81) and isolated MVR (<80: 6 [3.4%] vs. ≥80: 1 [2.8%], p  > .99) groups were similar. Age >80 years did not influence in‐hospital mortality (hazard ratio [HR], 1.07; 95% confidence interval [CI], 0.36–3.14, p  = .9), stroke (HR, 1.12; 95% CI, 0.19–6.71, p  = .9), hemodialysis (HR, 1.44; 95% CI, 0.45–4.66, p  = .54), or prolonged ventilation (HR, 1.61; 95% CI, 0.81–3.23, p  = .18), but influenced the incidence of reopening for bleeding (HR, 3.97; 95% CI, 1.11–14.19, p  = .03). Cox proportional hazard model results showed that age >80 years did not affect cardiac death (HR, 1.45, 95% CI: 0.67–3.12, p  = .35), bleeding events (HR, 1.89, 95% CI: 0.84–4.27, p  = .13), or stroke (HR, 1.51, 95% CI: 0.54–4.21, p  = .44) during the follow‐up period. Conclusions: The perioperative and follow‐up outcomes of MVR in octogenarians were not inferior to those of younger patients. We should not hesitate to conduct MVR on the grounds of old age.